2014
DOI: 10.1007/jhep04(2014)085
|View full text |Cite
|
Sign up to set email alerts
|

A first look at Bottomonium melting via a stochastic potential

Abstract: Abstract:We investigate the phenomenon of Bottomonium melting in a thermal quarkgluon plasma using three-dimensional stochastic simulations based on the concept of openquantum systems. In this non-relativistic framework, introduced in [1], which makes close contact to the potentials derived in effective field theory, the bb system evolves unitarily under the incessant kicks by the constituents of the surrounding heat bath. In particular thermal fluctuations and the presence of a complex potential in the EFT ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…Studies of bottomonium in perturbative pNRQCD have shown however that the imaginary part contains both contributions from gluodissociation and Landau damping, which leads to the excitation of bottomonium states without decay of the QQ pair. Eventually we will need to understand how to disentangle these two contributions, since the latter, as shown in exploratory studies in the context of open-quantum systems [80,81] leads to a weaker suppression. That is, our inability to disentangle the underlying mechanisms of the imaginary part has led us to assign it fully to a loss channel which may overestimate the actual suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of bottomonium in perturbative pNRQCD have shown however that the imaginary part contains both contributions from gluodissociation and Landau damping, which leads to the excitation of bottomonium states without decay of the QQ pair. Eventually we will need to understand how to disentangle these two contributions, since the latter, as shown in exploratory studies in the context of open-quantum systems [80,81] leads to a weaker suppression. That is, our inability to disentangle the underlying mechanisms of the imaginary part has led us to assign it fully to a loss channel which may overestimate the actual suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in this field include a formulation of a Lindblad type coupled dynamics for color singlet and octet degrees of freedom [83][84][85], which has been evaluated in a perturbative setting in [86]. A first attempt to describe bottomonium dynamics was presented in [80], however, the medium evolution used in this paper was not yet realistic.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to extract the survival probability associated with the thermal-noise averaged quantum wave-function, however, does not fully take into account in-medium transitions between different singlet/octet and angular momentum states. There is currently ongoing work to include true stochastic noise at the level of the real-time Schrödinger equation solution, either through explicit noisy potentials [26,27,31,[84][85][86][87][88] or through solution of the Lindblad equation for the reduced density matrix [28,30,[32][33][34]. Preliminary results obtained using the quantum trajectories method to solve the Lindblad equation indicate that more accurate inclusion of noise effects including, e.g., in-medium singlet-octet transitions, will result in only small changes in R AA [Υ(1s)] [89].…”
Section: Jhep03(2021)235mentioning
confidence: 99%
“…9 The lattice in-medium potential can also be used to setup a description of the realtime evolution of the heavy quarkonium wave function at finite temperature in the context of open quantum systems. An approach based on a stochastic potential [26][27][28][29] appears promising, where a purely real potential, given by Re[V] is randomly perturbed at each time step by noise of strength related to Im [V]. If developed further it promises to provide vital and phenomenologically relevant information on e.g.…”
Section: Jhep12(2015)101mentioning
confidence: 99%